Sejarah Penjaminan Ekonomi Industri Halal Di Indonesia - Malahayatie, Malahayatie; Qusairy, Rayhan; Maulana, Nora (Al-Sharf: Jurnal Ekonomi Islam, 2024)
This research is important because it contributes to identifying policies, regulations, and implementation that have taken place in the community. So that the results of the study can be useful in assisting policy makers in developing various policies and programs that are more effective in the future. This study uses qualitative methods and historical analysis by identifying key factors that can hinder the growth of the halal industry. Such as social change, consumer attitudes towards halal products, and support from the government and financial institutions. In addition, this study also highlights the role played by halal certification bodies in the process of ensuring compliance with halal standards and how advances in technology and digitalization can affect the efficiency, growth and transparency of the halal industry. The findings show that the halal industry is not only important for the Muslim community. It is also important for consumers around the world who are looking for high quality and unique goods. The results of this study also show that the need for a race in the halal industry sector, both in terms of regulations, programs and other roles. Starting from the government, private institutions, and the community. So that it can trigger a more optimal halal industry sector in various halal sectors, in an effort to support a stable and intuitive rate of economic growth.